A Rumination-Focused Cognitive-Behavioral Therapy Self-Help Program to Reduce Depressive Rumination in High-Ruminating Japanese Female University Students: A Case Series Study. Issue 2 (May 2022) - Umegaki, Yusuke; Nakagawa, Atsuo; Watkins, Edward; Mullan, Eugene
Highlights: Rumination, worry, and anxiety reduced after receiving RFCBT self-help. A larger number of modules completed consolidated the improvement. Increased awareness, concrete thinking, and compassion were reported to be helpful. Abstract: The present case series reports the preliminary test of a rumination-focused cognitive-behavioral therapy (RFCBT) self-help program to reduce depressive rumination among Japanese female undergraduates. A workbook-type self-help program based on RFCBT was implemented with 39 participants showing a high tendency toward rumination/worry. Data from 30 participants who completed one or more modules were analyzed quantitatively. The results showed significant reductions of rumination, worry, and anxiety at post-intervention. Further, semistructured interviews were conducted with 13 participants who completed the program, and verbatim data were examined using content analysis. The contents found to be useful and difficult differed for each participant and each module. Based on these results, the future implementation and dissemination of RFCBT is discussed.